68Ga-DOTA-DiPSMA PET/CT Imaging: Biodistribution, Dosimetry, and Preliminary Application in Prostate Cancer - Zhang, Jiaying; Lin, Zefang; Zhang, Xiaojun; Lin, Rong; Cui, Mengchao; Miao, Weibing; Yao, Shaobo (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose This prospective trial aimed to evaluate the safety, dosimetry, biodistribution, of a novel theranostic probe 68Ga-DOTA-DiPSMA. Also, we have performed the first preliminary application with 68Ga-DOTA-DiPSMA in prostate cancer (PCa) patients. Methods Five healthy volunteers and ten PCa patients were injected with an intravenous bolus of 68Ga-DOTA-DiPSMA. They received serial whole-body PET scans from the time of injection up to 60 min post-injection, with a second PET/CT scanning at 120 min post-injection. In PCa patients, low-dose CT scan, whole-body PET was performed with 2 min per bed position in 40 min post-injection. Absorbed organ doses and effective doses were calculated using OLINDA/EXM. Normal organ uptake and tumor lesion uptake were measured. A lesion-by-lesion analysis was performed. Results 68Ga-DOTA-DiPSMA administration was safe and well-tolerated. The kidneys received the highest absorbed dose (114.46 ± 29.28 uSv/MBq), followed by the urinary bladder wall (100.82 ± 46.22 uSv/MBq) in accordance with the expected Prostate-Specific Membrane Antigen (PSMA) renal excretion of the tracer. The mean effective dose was 19.46 ± 1.73 μSv/MBq. The SUVmax of 68Ga-DOTA-DiPSMA PET/CT for PCa lesions, bone metastases, and lymph node metastases were 4.41 ± 2.72, 2.95 ± 1.11 and 3.26 ± 1.20, respectively. Conclusion Injection of 68Ga-DOTA-DiPSMA is safe and associated with low absorbed and effective doses. 68Ga-DOTA-DiPSMA shows favorable kinetics and imaging characteristics in patients that warrant further head-to-head comparison to validate 68Ga-DOTA-DiPSMA as an alternative for gallium-68-labelled PSMA clinical PET. Low non-specific uptake in normal organs of 68Ga-DOTA-DiPSMA indicates potential radioligand therapy (RLT) application when labeled with 177Lu, 90Y, or 225Ac.